Ecometabolomic investigation of abiotically induced phytochemical change to invasive heather, Calluna vulgaris and its influence on the biocontrol agent Lochmaea suturalis : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Ecology at Massey University, Palmerston North, New Zealand - Barrett, D. Paul (Massey University, 2026)
Invasive plants represent one of the most pressing environmental issues globally. They pose a serious threat to terrestrial ecosystem function, loss of biodiversity, economic wellbeing and food security. Biological control of invasive plants is a well-founded and in many cases successful management option against these threats but in some cases, the control agents fail and do not establish or are ineffective if they do. Relevant literature maintains that abiotic and biotic influences can be responsible for failed biocontrol programmes. However, a largely unexplored reason for these failures could involve abiotically induced changes to an invasive plants’ biochemical phenotype, which may consequently enhance resistance against the biocontrol agent. Understanding invasive plant biochemical phenotypic change, and the environmental influences determining them, could provide valuable information to assist with control agent and site selection or to retrospectively elucidate failures or ineffectiveness. Plant metabolomics studies plant biochemistry at the molecular level, providing a non-targeted characterisation and quantification of both known and unknown metabolites (the metabolome) in a particular tissue in response to its environment. This technique combines analytical chemistry, bioinformatics and multivariate statistics, allowing characterisation and identification of plant biochemical profiles and phenotypes. A literature review provides little evidence however that this technology is being applied to support weed biocontrol programmes. Heather beetle, Lochmaea suturalis (Thomson, 1866), introduced to control invasive heather Calluna vulgaris (L.) Hull in the Central Plateau (CP) region of New Zealand (NZ) was difficult to establish and displays variable effectiveness. This provides an ideal model system to apply metabolomic technology and to test hypotheses relating to potential changes in the heather metabolome in its invaded environment. Using UHPLC-MS/MS based non-targeted metabolomics, I analysed primary and secondary metabolites of C. vulgaris from its native range in the United Kingdom (UK) and its introduced range (NZ), between which, differences in soil nutrients and ultraviolet light exist. I also explored secondary metabolite variation between sites that differ in soil nutrient profiles within each range. New Zealand samples had the greatest number of amplified metabolites, most notably defensive phenylpropanoids and evidence of upregulation of key biosynthetic pathways. Secondary metabolite variation within each range revealed differences between sites but found little correlation of phenylpropanoid levels being influenced by variable soil nutrients. Ultra-violet (UV) radiation is a known driver of alterations to secondary metabolites in plants. On the CP, UV intensity is double that of the plants native range in the UK. Heather was experimentally exposed to 20% and 95% attenuation of UV and the secondary metabolite responses were recorded. This treatment demonstrated significant alterations to many compounds derived from the shikimate-phenylpropanoid pathway. Using plants from each treatment, bioassays were performed measuring prepupal weight and survival of L. suturalis. The results demonstrate significant UV-induced alterations to several compounds in heather but no significant difference in the beetle life history parameters. Evidence exists that heather beetle performance and establishment improves with increased foliar nitrogen (N) in heather. A question remained whether this is due solely to increased foliar N or, additionally, to changes to the defensive metabolites of the plant. A field-based experiment using artificial fertilizer to increase soil nutrient availability was established. Foliar total carbon (C) and N, and primary and secondary metabolite responses in C. vulgaris foliage were quantified, revealing several amplified primary nitrogen containing metabolites and a decrease in  68% of secondary phenylpropanoids. This result suggests that nutrient stress increases the foliar C:N ratio resulting in increased carbon-rich defensive metabolites and decreased N-containing metabolites. This in turn reduces the efficiency of conversion of ingested food (ECI) index and thus is likely the main driver of poor performance of L. suturalis in the CP environment. The results of these metabolomic investigations demonstrate the highly complex interactions that exist between abiotic parameters, plant metabolome and insect herbivore responses. Understanding these complexities could have an important role to play in future biological control of weeds programmes and perhaps be applied to improve success rates or retrospectively elucidate and/or resurrect problematic ones.
Keywords: Metabolomics; Biocontrol; Phytochemistry; Plant defense; Calluna vulgaris; 31 Biological sciences::3108 Plant biology::310802 Plant biochemistry; 41 Environmental sciences::4102 Ecological applications::410202 Biosecurity science and invasive species ecology